AnatomyMR: A Multi-User Mixed Reality Platform for Medical Education. (November 2019) - Murugan, Amarnath; Balaji, Ganesh.A; Rajkumar, R.
Abstract: Mixed Reality (MR) has opened up new means of imparting education, especially in the medical field. Students could view the whole human anatomy and it's components at multiple levels of scale to learn their location and naming nomenclature, and also interact with them separately to familiarize themselves with their functions. In this paper we propose a platform for Medical education in MR which creates shared experiences, providing support for teaching within classrooms. The application would also work as a standalone experience, augmenting important information over the anatomy model for the student's reference when a shared experience is not in session, thereby facilitating self-study. The platform would be built in such a way that the instructors would also have the option to add 3D models and relevant content to the existing courseware and have it rendered in the mixed reality space.